O-150 Myocardial infarction incidence rates among night workers in the Danish health care sector: exposure-response relations. (14th March 2023) - Vestergaard, Jesper Medom; Dalbøge, A; Bonde, JP; Garde, AH; Alba Hidalgo, Miguel Angel; Hansen, ÅM; Larsen, A; Härmä, M; Costello, S; Böttcher, M; Alba Hidalgo, Miguel Angel
Abstract : Introduction: Night shift work has been associated with cardiovascular disease. We examined the exposure-response relation between number of monthly night shifts, other quantitative night work characteristics and myocardial infarction. Material and Methods: We followed a cohort of 100 784 nurses, physicians and other health care workers working night shifts at Danish public hospitals in Denmark (80% women), 2007–15, with day-by-day work hour information from a national payroll register. First time hospital admission rates for myocardial infarction were identified. We analysed data with Poisson regression adjusting for register-based potential confounders (age, diabetes, obesity, hypercholesterolemia, hypertension, family-history of cardiovascular disease, occupation, education, and evening work). Results and Conclusions: During follow-up, 397 night workers (56% women) were diagnosed with first time myocardial infarction. For female night shift workers, we observed exposure-response relations for number of monthly night shifts, cumulative night shifts, and consecutive night shifts, but not for years with rotating night shifts or years with any night shifts. For male night shift workers, we observed no exposure-response relations. Several measures of increasing extent of night shift work were among women night workers related to an increasing risk of myocardial infarction. No such patterns were observed among men. This may indicate a sex specific effect of night shift work.